Meio ambiente e a empresa: o mapeamento dos stakeholders relevantes na gestão ambiental das indústrias fluminenses - Medeiros, Luis Cláudio Meirelles de (2003)
This study aims to analyze the complex relationship between firms and stakeholders in Rio de Janeiro' s industries. This study focused on the analysis of the influence of the stakeholders engaged in enviromental management in the state of Rio de Janeiro. The first session is aimed at synthesizing the trajectory of the environment movement in the world and in Brazil. The second session aims to present a research in Rio de Janeiro' s industries.